Antifungal Activities of Certain Components of Teak Wood Extractives - Ganis Lukmandaru (Masyarakat Peneliti Kayu Indonesia, 2013)
The present research was aimed to evaluate the antifungal activities of teak (Tectona grandis) extracts and their components against Trametes versicolor, Fomitopsis palustris, Rhizopus oryzae, Cladosporium cladosporioides, and Chaetomium globosum. In this study, wood meal of 72 years old teak heartwood was successively refluxed with n-hexane, ethyl acetate and methanol. Bioassay-guided investigation by measuring the growth rate of each fungus on potato dextrose agar (PDA) medium led to the fractionation of n-hexane soluble extract. Column chromatographic fractionations resulted in the isolation of tectoquinone, deoxylapachol, squalene and an unknown compound (C1). The n-hexane and EtOAc extracts were potent mycelial growth inhibitors for R. oryzae (76-78%) and C. cladosporioides (65-73%), while MeOH extract had higher antifungal activities against both T. versicolor (80.2%) and C. globosum (83.3%). In the compound levels, the results were varied, in which deoxylapachol could inhibit all fungi species except for the C. globosum, while tecquinone merely deterred the growth of R. oryzae (58.9%). Squalene and C1 were growth inhibitors to C. cladosporioides (50-63%).Key words: antifungal activities, deoxylapachol, extractive, Tectona grandis, tectoquinone